Freedom in the wilderness: A study of a Darknet space. (June 2020) - Graham, Roderick; Pitman, Brian
Mass media and journalistic accounts of Darknets have focused disproportionately on their criminogenic aspects. Moreover, research has focused mainly on the Darknet technology Tor. We wish to expand scholars' knowledge of Darknets by exploring a different Darknet technology, Freenet. Using a combination of content analysis and grounded theory, this research asked three progressively complex questions. First, we asked: What are the types of content and the distribution of content on Freenet ? Our findings show that Freenet fosters a singular distribution of content, with a high ratio of blogs (or flogs), child pornography, empty links, and Web 1.0 websites that archive information. We assumed that this content is not discrete points of data but instead produce sociologically interesting phenomena. Therefore, we ask: What are the content patterns on Freenet? Four patterns were identified. Freenet is (1) an archive of deviant data resistant to censorship, (2) a space dominated by content associated with masculinity, (3) a nonmarket space where commercial exchange is nonexistent, and (4) an empty space with many requests not returning information, and many flogs abandoned. We asked a third question: How does the analysis of Freenet inform current understandings of hacker culture? Freenet, we suggest, can be understood as a type of digital 'wilderness'. It is a singular Darknet space, supporting a distinct set of hacker practices.